KOMPETENSI KEWIRAUSAHAAN KEPALA SEKOLAH DALAM MENGEMBANGKAN EDUPRENEURSHIP DI SEKOLAH MENENGAH KEJURUAN - yulia (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
The study aims to analyze the implementation of edupreneurship that has taken place in four vocational schools in Bantul, as well as the effectiveness of the entrepreneurial competence of principals for the implementation of edupreneurship and the impact of the entrepreneurial competence of principals on the edupreneurship development program. This type of research is descriptive qualitative. Data collection techniques with interviews, observation, documentation The results of the study indicate that the implementation of edupreneurship that has taken place in four vocational schools in Bantul has generally been going well. This is due to the presence of human resources who have a high commitment and work ethic to think creatively. The entrepreneurial competence of school principals is very effective in encouraging the implementation and development of edupreneurship in vocational schools. The entrepreneurial competence of school principals has a very good impact on the edupreneurship development program in vocational schools; the growth and development of business units in each skill competency in the form of products and services; the formation of teaching factories in vocational schools; in collaboration with IDUKA as a real project from the industry carried out by students; and the formation of a market school-facilitated place for product marketing.